1998
DOI: 10.1038/sj.bjp.0701804
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel melanocortin4 receptor selective MSH analogues

Abstract: 1 We synthesized a novel series of cyclic melanocyte stimulating hormone (MSH) analogues and tested their binding properties on cells transiently expressing the human melanocortin 1 (MC 1 ), MC 3 , MC 4 and MC 5 receptors. 2 We discovered that compounds with 26 membered rings of [Cys 4 ,D-Nal 7 ,Cys 11 ]a-MSH(4 ± 11) displayed speci®c MC 4 receptor selectivity. The preference order of the di erent MC receptor subtypes for the novel [Cys 4 D-Nal 7 Cys 11 ]a-MSH(4 ± 11) analogues are distinct from all other know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…These modifications have suggested that amino acid residues at the 6 (His), 7 (Phe), 8 (Arg), and 9 (Trp) positions are important for molecular recognition and activation of the melanocortin receptors. In particular, positions 6 and 7 of cyclic and of linear derivatives of α-MSH appeared to be important for high affinity and selectivity at hMC3 and hMC4 receptors [1,17,26,36,39,41].…”
Section: Resultsmentioning
confidence: 99%
“…These modifications have suggested that amino acid residues at the 6 (His), 7 (Phe), 8 (Arg), and 9 (Trp) positions are important for molecular recognition and activation of the melanocortin receptors. In particular, positions 6 and 7 of cyclic and of linear derivatives of α-MSH appeared to be important for high affinity and selectivity at hMC3 and hMC4 receptors [1,17,26,36,39,41].…”
Section: Resultsmentioning
confidence: 99%
“…, and Phe 12 of ␥-MSH, Schioth et al (39) suggested that the ␥-MSH C terminus hinders MC4R binding. However, this peptide showed an equal loss of affinity for the MC3R.…”
mentioning
confidence: 99%
“…SHU9119 is a potent melanocortin MC 3 and melanocortin MC 4 receptor antagonist with IC50 values of 1.2 and 0.36 nM respectively (Schioth et al, 1998). AgRP is an inverse agonist that binds with similar affinities to melanocortin MC 3 and melanocortin MC 4 receptors (K i ¼3.3 and 2.6 nM respectively (Yang et al, 1999)).…”
Section: Discussionmentioning
confidence: 99%